Feminist utopian novels of the 1970s : Joanna Russ & Dorothy Bryant - Teslenko, Tatiana (Literary criticism and cultural theory., 2003)
This work presents an exploration of the reinvented utopia that provided second-wave feminists of the 1970s with a conceptual space to articulate the politics of change.